Analisis Metode Pembelajaran Kooperatif Dalam Mengasah Kemampuan Mahasiwa menulis Opini yang Kritis dan Relevan di media Massa. - Kasih Kasih (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the effectiveness of the cooperative learning method in enhancing the ability of students at Pamulang University (UNPAM) to write critical and relevant opinion articles for mass media. The cooperative learning method was chosen because it is considered effective in fostering collaboration, discussion, and the exchange of ideas among students, key elements in producing high-quality opinion writing. This research employs a qualitative approach using a case study method. Data were collected through observations, in-depth interviews, and document analysis of students’ opinion articles. The research subjects were students of the Indonesian Language Study Program at UNPAM who were enrolled in the Creative Writing course. The findings indicate that the cooperative learning method effectively improves students’ abilities to formulate arguments, organize essay structures, and develop a persuasive writing style. Furthermore, group collaboration helped students broaden their perspectives and increase their confidence in expressing opinions. This study is expected to serve as a reference for developing more effective methods of teaching opinion writing at the university level.